Cross-level effects of HRM bundle on employee well-being and job performance: The mediating role of psychological ownership. Issue 3 (7th August 2017) - Liu, Fang; Chow, Irene Hau-Siu; Xiao, Dan; Huang, Man
Abstract : Purpose: The purpose of this paper is to examine the mediation role of psychological ownership for the organization (PO-O) in the relationships between human resource management (HRM) bundle and job satisfaction, affective commitment and job performance. Design/methodology/approach: Based on multilevel data analysis, 705 employees from 162 small- and medium-sized enterprises in China, this study adopted an empirical design. Findings: PO-O mediates the relationships between HRM bundle and job satisfaction, affective commitment and job performance. Research limitations/implications: These findings highlight the importance of HRM bundle to contribute to employees' feelings of ownership for the organization and their well-being and job performance. Longitudinal design and multiple sources at multi-stage for data collection in future research would be required for the further understanding of the relationships between the variables of this study. A single organizational and cultural context is not sufficient; broader testing in different organizational and cultural contexts is required. Practical implications: Managers should develop employees' feeling of ownership by using HRM bundle. They can thus gain a competitive advantage by enhancing employees' skills, knowledge and abilities, as well as improving their well-being and performance. Originality/value: This study extends the current literature by providing theoretical and empirical explanations of the mediating role of psychological ownership in the HRM bundle-employee outcomes relationship using a cross-level research design.